PENGEMBANGAN BAHAN AJAR BUSMEGA (BUKU SERI MATEMATIKA KELAS TIGA) UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Ulfa, Nanik; Fauziyah, Nabilatul (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
This study to determine the effectiveness of BUSMEGA teaching materials (Buku Seri Matematika Kelas Tiga) to improve student learning outcomes of MI Bahrul Ulum Pakisaji. The type of research used by the author is the Research and Development (R&D) research method, where this research produces a particular product and tests the feasibility of the product being developed. As for the development model, researchers use the ADDIE model which includes Analysis, Design, Development, Implementation, Evaluation. The results of the study show that BUSMEGA's teaching materials are appropriate as teaching materials. Evidenced by the percentage of material expert validation results of 90% and design experts 75.6% declared feasible. Meanwhile, student learning outcomes increased by up to 50%. The effectiveness of teaching materials can be seen in the manual t-test with a significance level of 0.05, the results obtained are tcount ≥ ttable, namely 3.76 ≥ 1.734, which means H0 is rejected and Ha is accepted. Thus, there are significant differences in the implementation of BUSMEGA teaching materials. This shows that BUSMEGA's teaching materials are appropriate for use and can improve student learning outcomes for 3 Madrasah Ibtidaiyah.